2018
DOI: 10.24297/jab.v11i1.7590
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bio-Fertilizers Azotobacter Chroococcum and Pseudomonas Fluorescens on Growth of Broccoli (Brassica Oleracea L. Var. Italica)

Abstract: A field experiment was carried out at the experimental farm of soil laboratory belong to Directorate of Diyala Agriculture, Iraq during 2017. The experiment comprises of different doses of biofertilizers (Azotobacter chroococcum and Pseudomonas fluorescens) 0.08, 0.14 and 0.28 g/plant to assess their performance on growth characteristics of broccoli. The experiment was laid out in randomized complete block design having four treatments with three replications. The data analysis revealed that the maximum of lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…According to studies with similar results to our study, In a study; Biofertilized plants from bacterial colonization showed higher vegetative growth parameters (plant height, number of leaves, number of branches, as well as fresh and dry weight of leaves and stems) than untreated plants. Kumaraswami and Madalgeri [12].…”
Section: Resultsmentioning
confidence: 99%
“…According to studies with similar results to our study, In a study; Biofertilized plants from bacterial colonization showed higher vegetative growth parameters (plant height, number of leaves, number of branches, as well as fresh and dry weight of leaves and stems) than untreated plants. Kumaraswami and Madalgeri [12].…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that Azospirillum and Azotobacter bacteria produce adequate amounts of cytokinins and Auxins (IAA) which accelerates plant growth by increasing the uptake of nutrients from the soil and increasing length of branches and roots [35,36]. A combination of Azotobacter chroococcum with Pseudomonas fluorescens was reported to improve broccoli growth [37]. Sarhan reported a positive effect of Azotobacter on growth and yield of potato plants [38].…”
Section: Discussionmentioning
confidence: 99%
“…For grain yield (tons ha -1 ), the grains and hay isolated per square meter harvested in each experimental unit had the grains weighed and converted into tons per hectare. The harvest index (%) computation employed the following equation (Salim et al, 2019):…”
Section: Data Recordedmentioning
confidence: 99%